Effect of plasmodium yoelii exposure on vaccination with the 19-kilodalton carboxyl terminus of merozoite surface protein 1 and vice versa and implications for the application of a human malaria vaccine - Jiraprapa Wipasa (2018)
It is well known that exposure to one antigen can modulate the immune responses that develop following exposure to closely related antigens. It is also known that the composition of the repertoire can be skewed to favor epitopes shared between a current infection and a preceding one, a phenomenon referred to as "original antigenic sin." It was of interest, therefore, to investigate the antibody response that develops following exposure to the malaria vaccine candidate homologue Plasmodium yoetii MSP1 19 in mice that had previously experienced malaria infection and vice versa. In this study, preexposure of mice to Plasmodium yoelii elicited native anti-MSPl 19 antibody responses, which could be boosted by vaccination with recombinant MSP1 19. Likewise, infection of MSPl 19-primed mice with P. yoelii led to an increase of anti-MSPl 19 antibodies. However, this increase was at the expense of antibodies to parasite determinants other than MSP1 19. This change in the balance of antibody specificities significantly affected the ability of mice to withstand a subsequent infection. These data have particular relevance to the possible outcome of malaria vaccination for those situations where the vaccine response is suboptimal and suggest that suboptimal vaccination may in fact render the ultimate acquisition of natural immunity more difficult. Copyright © 2009, American Society for Microbiology. All Rights Reserved.